Perforating metastatic melanoma - Takenobu Ohashi; Nobuyuki Kikuchi; Yuka Hanami; Takako Miura; Mikio Otsuka; Toshiyuki Yamamoto (Our Dermatology Online, 2015)
We describe a case of metastatic malignant melanoma on the thigh with comedo-like appearance, which histologically showed elimination of tumor cells. A 70 year-old man was diagnosed with a nodular type malignant melanoma involving the lower back with satellite lesions (stage IIIB, T4b N2c M0, Breslow's tumor thickness; 10.3 mm, Clark's level; IV).